KEY FACTORS INFLUENCING THE PARTICIPATION OF LOCAL HOUSEHOLDS IN REDD+ PROGRAM: A CASE STUDY IN VIETNAM - Dinh Hai, Le; Thi Lan Phuong, Hoang (Journal of Forestry Science and Technology, 2019)
Nowadays, climate change is serious problem in worldwide. Deforestation of tropical forests contributes approximately 10 - 20% of global greenhouse gas emissions. In order to build the capacity of developing countries to encounter the challenges of reducing emissions from deforestation in developing countries (REDD), we need find key factors influencing the participation of local household in REDD+ program. From 2009 to 2012, the Japan International Cooperation Agency combined with Vietnam Administration of Forestry to develop REDD+ program in Dien Bien province. We conducted a survey of 150 households in Muong Phang commune, Dien Bien district, Dien Bien province. Results of the study show that six main factors, including: forestland area, ethnicity, concerned about forest degradation, household wealth ranking, rationality of government payment, and number of labourers, significantly influence participation of local households to REDD+ program in the study area. The study also indicates some potential solutions to increase the number of people participating REDD+ program.